Prevalencia de Sarcoma de Kaposi en pacientes VIH positivo. Hospital Carlos Andrade Marín, 2019 - Narváez Guamán, Angélica Lizeth (2020)
Kaposi's sarcoma is a neoplasm or abnormal formation of lymphatic endothelial cells of an individual. To date, four clinical types have been described, such as: classic, endemic or African, epidemic or associated with HIV and iatrogenic. Whose main diagnostic mechanism is histopathological. In the present investigation it was established to determine the prevalence of Kaposi's Sarcoma in HIV positive patients who attend Carlos Andrade Marín Hospital during the period January - August 2019, as well as to present the prevalence of cases with Kaposi's Sarcoma in HIV positive patients. Describe the presence of Kaposi's Sarcoma by age and sex in patients with HIV and identify the presence of Kaposi's Sarcoma based on sex in HIV patients. A descriptive, observational and retrospective cross-sectional study was developed. The population was made up of 2,624 patients who attended Carlos Andrade Marín Hospital for the modalities of external consultation, emergency and hospitalization during the period from January to August 2019. The results obtained allowed to determine a prevalence of 2% of Kaposi's Sarcoma in a sample with a high percentage of men, 85% with regard to women 15%, with a predominance of cases between the ages of 20 to 39 and 40 to 64, with a greater amount of male sex.